Analysis of scientific research groups with greater productive applicability in Brazil: capacities and interactions with firms - Caliari, Thiago; Chiarini, Tulio (Universidad del Pacífico, 2018)
This paper analyzes the capacities of BR Survey Research Groups in generating science and technology, and how these groups may be associated with university-firm interactions. To this end, we perform a classification based on the diagram proposed by Stokes (2005), using the qualitative comparative analysis (QCA) statistical technique. As a primary result, we find that scientific and technological capacity on the part of the research groups is not a necessary condition for interactions with companies. Indeed, some research groups without high scientific and technological capacity make more interactions (in terms of the total amount) and yield similar values in the analysis (relative to the number of researchers) in comparison with the most qualified groups: those located in Pasteur’s quadrant.